Family Literacy Practices: Adults’ Dual Roles of Student and Teacher in the Literacy Development of Their Children - Rose Santos (Adult Education Research Conference, 2008)
The purpose of this round table is to engage the audience in discussions about the literacy practices of families where the adult learner is also the teacher of literacy in the home. It will call attention to the dual roles of the parent as student and teacher of literacy and the challenges and opportunities inherent in such practices.
Keywords: family literacy practices